Erosion of rock with a water jet - Rehbinder, Göran (Luleå tekniska universitet, 1977)
During the last decade destruction of rock with the aid of a high speed water jet has been the subject of great interest. Most papers published in this field deal with experiments but very little has been done theoretically. It has generally been assumed that when a water jet hits the face of a rock this case is quite equivalent to the case when a bit is pressed into the rock, which means that the destruction of the rock is a fracture process caused by stresses. There are however some simple experiments that clearly indicate that this approach is incorrect. The results of the investigation presented here indicate that in rock destruction with a high speed water jet the relevant rock parameters are quite different from those of mechnical rock destruction. The author has shown with the aid of both theory and experiments that from erosion point of view a rock is characterized by two quantities, erosion resistance and threshold pressure. The entire work is presented in three Research Reports from the University of Luleå: 1. Rehbinder, G: Erosion of rock with a water jet. Some fundamental investigations concerning the mechanism of erosion. Research Report, TULEA 1977:02, University of Luleå 2. Rehbinder, G: Slot cutting in rock with a high speed water jet. Research Report, TULEA 1977:03, University of Luleå 3. Rehbinder, G: A water zone propagating through a permeable rock. Research Report, TULEA 1977:04, University of Luleå. Godkänd; 1977; 20070503 (ysko)